Public management reform and administrative law in local public service in the UK - McEldowney, John (2003)
Local government has been subject to intensive change and extensive legislation since the 1970s and the government of Mrs. Thatcher intended to reduce public expenditure. Since the election of the new Labour government in 1997, modernization and reform continues in the development of public services in local government. Recent reform of local government has been complicated by the introduction, since 1998, of devolution to the London Assembly with an elected mayor, assemblies in Northern Ireland, Wales and the Scottish Parliament. There are complicated financial relations between local government and the different varieties of devolved government. The United Kingdom remains a unitary rather than a federal state but devolution delivers a level of decentralization. Central government retains control through legal and economic instruments and provides local government with limited autonomy. The elected element in local government contributes to local democracy. Local government provides an important element in the delivery and management of public services but complicated by the fact that privatization has changed the way public services are delivered. There are a plethora of statutes, regulations, guidance and audit systems that provide a comprehensive framework for local government in the provision of education, social services, planning public health and licensing regulation. The courts have exercised an oversight of local government through judicial review of disputes between local and central government. as local government must act within its legal powers the legality of its decisions must be in accordance with the law. Local government is expected to become more responsive to local needs and citizenship panels exist to provide input from the local community. Local authorities have contributed to the development of judicial review through a number of landmark decisions and in common with other public bodies, local authorities are expected to conform to the Human Rights Act 1998. The latest Local Government Bill 2002 proposes to identify excellent local authorities who will be rewarded with freedom to act outside the controls of central government. - Reproduced.
Keywords: Administrative law - Great Britain; Administrative reform - Great Britain; Administrative reform